Space Allowance of the Littered Area Affects Lying Behavior in Group-Housed Horses - Burla, Joan-Bryce; Rufener, Christina; Bachmann, Iris; Gygax, Lorenz; Patt, Antonia; Hillmann, Edna (Frontiers in Veterinary Science, 2017)
Horses can sleep while standing, however, recumbency is required for REM sleep and therefore essential. Previous research indicated a minimal duration of recumbency of 30 minutes per 24 hours to perform a minimal duration of REM sleep. For group-housed horses, suitable lying area represents a potentially limited resource. In Switzerland, minimal dimensions for the space allowance of the littered area are therefore legally required. To assess the effect of different space allowances of the littered area on lying behavior, 38 horses in eight groups were exposed to four treatments for 11 days each; T0: no litter provided, T0.5: 0.5x minimal dimensions, T1: minimal dimensions, and T1.5: 1.5x minimal dimensions. Non-littered areas were covered with hard rubber mats. Lying behavior was observed during the last 72 hours of each treatment. The total number of lying bouts per 24 hours was similar in treatments providing litter, whereas in treatment T0 recumbency occurred only rarely (F1,93 = 14.74, p = 0.0002) with the majority of horses lying down for less than 30 minutes per 24 hours (χ_1^2 = 11.82, p = 0.0006). Overall, the total duration of recumbency per 24 hours increased with increasing dimensions of the littered area, whereby the effect attenuated between treatment T1 and T1.5 in high-ranking horses but continued in low-ranking horses (F1,91 = 3.22, p = 0.076). Furthermore, low-ranking horses showed considerably more forcedly terminated lying bouts in treatments T0.5 and T1, but were similar to high-ranking horses in T1.5 (F1,76 = 8.43, p = 0.005). Nonetheless, a number of individuals showed durations of recumbency of less than 30 minutes per 24 hours even in treatment T1.5. The lying behavior was dependent on the availability of a soft and deformable surface for recumbency. A beneficial effect of enlarged dimensions of the littered area was shown by increased durations of recumbency and decreased proportion of forcedly terminated lying bouts in low-ranking horses. Taking this into account, it became evident that the minimal dimensions for the littered area as implemented in the Swiss animal welfare legislation do not ensure undisturbed lying behavior for all members of a given group.